The Relationship Between Perfectionism and Quality of Sleep: A Cross‐Sectional Study Among Sudanese Medical Students - Mohamed H. Elbadawi; Amr A. Mubasher; Alaa A. Abdulgalil; Aya Alsaid; Nafisa Elameen; Ragad Magdi; Waad A. Mohamed; Mohamed H. Fadul (Health Science Reports, 2025)
ABSTRACT Background and Aims Perfectionism is the pursuit of perfection, the imposition of unreasonably high standards, and a constant state of self‐criticism. Perfectionism, which can lead to depression, obsessive‐compulsive disorder, and anxiety, can affect the quality of sleep, thereby leading to less productivity. Medical students are more likely to develop sleep‐deprived lifestyles, which can be due to the stressful environment of medical school. This study primarily addresses the association between perfectionism among medical students and poor sleep quality. A secondary aim is to study the socio‐demographic differences based on gender and academic year. Methods This analytical and facility‐based cross‐sectional study was conducted between April and July 2023 at the Faculty of Medicine, University of Khartoum, Sudan. It used two validated questionnaires: the Frost Multidimensional Perfectionism Scale (F‐MPS) and the Pittsburgh Sleep Quality Index (PSQI). Data were collected using an online self‐administered questionnaire via social media platforms. Data Analysis was performed using SPSS version 21, employing descriptive statistics, univariate analysis, and regression. Results Of 233 medical students included in the study, almost 60% of the sample suffered from poor sleep quality. No significant mean differences were observed in gender or age in relation to perfectionism or sleep quality. Only two domains of perfectionism were found to be significantly associated with poor sleep quality: “concerns over mistakes and doubts of action” and “concern with parental expectation and evaluation” (p < 0.001 for both domains). There was a positive and significant association between the total perfectionism scale and sleep quality (r = 0.222, p < 0.001), meaning that higher perfectionism scores were found to be associated with poor sleep quality. Conclusion Our study highlighted the small, positive, and significant association between total perfectionism and sleep quality. Neither gender nor academic year appeared to contribute to this association. Therefore, this study reveals the effect of perfectionism on disturbing sleep quality, unbiased by either gender or academic year, with potential clinical and therapeutic applications that could benefit medical students.